FAST DISPERSION TECHNIQUES: APPROACHES AND RATIONALE FOR DEVELOPMENT OF FAST DISSOLVING TABLETS - admin pjmd; Anas M. Hanif; Ali Akbar Sial; Huma Ali; Farya Zafar; Anwar Ejaz Beg; Atta Ur- Rehman (ziauddin University, 2024)
Pharmaceutical companies have introduced several drug delivery systems in the field of Pharmaceutical sciences that provide better and faster therapeutic response in patients to modulate pain and inflammation. In the present article a detail on fast dissolving technique and suitability of dexibuprofen as model drug for such rapidly disintegrating formulations has been addressed. This review articles focuses on all aspects taken into consideration regarding formulation development parameters, technologies used, role of superdisintegrants incorporated and the latest advancement in the improvement of aforementioned drug delivery system to increase the patient compliance.